A recent‐onset ulcerated nodular plaque on the scalp. (29th May 2017) - Pathania, S.; Khullar, G.; De, D.; Chatterjee, D.; Saikia, U. N.; Handa, S.
Abstract : Clickhere for the corresponding questions to this CME article.